We are here with you hands in hands to facilitate your learning & don't appreciate the idea of copying or replicating solutions. Read More>>

Looking For Something at vustudents.ning.com? Click Here to Search

www.bit.ly/vucodes

+ Link For Assignments, GDBs & Online Quizzes Solution

www.bit.ly/papersvu

+ Link For Past Papers, Solved MCQs, Short Notes & More

MTH603 Numerical Analysis Friday, November 13, 2015 to Monday, November 16, 2015 GDB

Solve the equations x3 – 3x+ 0 in the interval [0,1] using the Regula Falsi Method(Method of False Position) up to two iterations.

Note that this is the graded GDB and you can post your solution of the given question only once. So before posting your solution preview it first.

You cannot directly type the mathematical symbols in discussion board forum so you have to use Math type software. A tutorial has been made for this purpose.

+ Click Here To Join also Our facebook study Group.

..How to Join Subject Study Groups & Get Helping Material?..


See Your Saved Posts Timeline

Views: 3538

.

+ http://bit.ly/vucodes (Link for Assignments, GDBs & Online Quizzes Solution)

+ http://bit.ly/papersvu (Link for Past Papers, Solved MCQs, Short Notes & More)

+ Click Here to Search (Looking For something at vustudents.ning.com?)

Replies to This Discussion

at this point i'm also confused

f(x)=x3−9x+1
f(2)=23−9(2)+1=8−18+1=−9
f(4)=43−9(4)+1=64−36+1=29
Sincef(2) andf(4) are of opposite signs, the root off(x) = 0 lies between 2 and 4.Takingx1 = 2,x2 = 4 and using Regula−Falsi method, the first approximation is given by
x3=x2−x2−x1f(x2)−f(x1)f(x2)=4−4−229−(−9)=4−2(29)38
=4−5838=4−1.5263=2.4736
Now
f(x3)=2.47363−9(2.4736)+1=−6.12644
Sincef(x2) andf(x3) are of opposite signs, the root lies betweenx2 andx3.
The second approximation to the root is given as
x4=x3−x3−x2f(x3)−f(x2)f(x3)=2.4736−2.4736−4−6.12644−29(−6.12644)
=2.4736−−1.5264−35.12644(−6.12644)=2.4736−(0.04345)(−6.12644)
=2.4736+0.26619=2.73989
Therefore
f(x4)=2.739893−9(2.73989)+1=20.5683−24.65901+1=−3.090707
Now, sincef(x2) andf(x4) are of opposite signs, the third approximation is obtained
from
x5=x4−x4−x2f(x4)−f(x2)f(x4)=2.73989−2.73989−4−3.090707−29(−3.090707)=2.86123
=2.73989−−1.26011−32.090707(−3.090707)=2.73989+0.039267(3.090707)=2.73989+0.121363=2.86125
Now
f(x5)=2.861253−9(2.86125)+1=23.42434−25.75125+1=−1.326868

May be two iterations are f(x3) and f(x4)

not sure

but i know that we have to solved just f(x3) and f(x4)

aoa 

Hira Anmol thanks to pointing out a mistake

Thanks to All :)

make change

Attachments:

not correct

plz share your gdb es mein copy ka drr na krein plz sb smjdar hain

Attachments:

not correct

why

RSS

© 2019   Created by + M.Tariq Malik.   Powered by

Promote Us  |  Report an Issue  |  Privacy Policy  |  Terms of Service